α-Glutathione S-Transferase, KIM-1, and Surfactant Protein-A as Predictive Biomarkers of Occupational Toxic Gas Exposure - Samar Kadhum Yousif; Hamid Jaddoa Abbas; Ibrahim Ahmed Nassar (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Occupational exposure to toxic gases in petroleum industries is associated with subclinical damage to hepatic, renal, and pulmonary systems, necessitating sensitive biomarkers for early detection. Specific Background: α-glutathione S-transferase (α-GST), kidney injury molecule-1 (KIM-1), and surfactant protein-A (SP-A) are proposed indicators of early organ-specific injury related to toxic exposure. Knowledge Gap: Limited studies have evaluated these biomarkers collectively as a predictive panel, particularly in high-risk populations such as petroleum workers in developing regions. Aims: This study assessed the prognostic value of α-GST, KIM-1, and SP-A as early biomarkers of occupational toxic gas exposure. Results: In a case-control study of 130 exposed workers and 56 controls, serum levels of α-GST, KIM-1, and SP-A were significantly higher in exposed individuals (p < 0.01). KIM-1 and SP-A showed increasing trends with longer exposure duration, while α-GST demonstrated site-specific variation. Logistic regression identified all three biomarkers as independent predictors of exposure. Novelty: The study provides integrated evidence supporting a multi-biomarker panel reflecting hepatic detoxification, renal tubular injury, and pulmonary epithelial response in occupational settings. Implications: These findings support the application of α-GST, KIM-1, and SP-A in early detection and occupational health monitoring, enabling improved risk stratification and surveillance in hazardous industrial environments. Highlights:• Elevated biomarker levels distinguish exposed workers from non-exposed controls• Duration-dependent increases observed in renal and pulmonary indicators• Combined biomarker panel predicts multi-organ response to workplace hazards Keywords: Occupational Toxic Gas Exposure, Alpha Glutathione S Transferase, Kidney Injury Molecule 1, Surfactant Protein A, Biomarkers